2013
DOI: 10.5327/z1519-874x2013000100006
|View full text |Cite
|
Sign up to set email alerts
|

Composição cianobacteriana e química dos estromatólitos da lagoa Salgada, Neógeno do estado do Rio de Janeiro, Brasil

Abstract: Disponível on-line no endereço www.igc.usp.br/geologiausp -95 -Resumo A lagoa Salgada é um corpo aquático costeiro, situada no norte do estado do Rio de Janeiro. A evolução geológica da lagoa está associada às oscilações do nível do mar durante o Neógeno e apresenta esteiras microbianas, estromatólitos estratiformes e estromatólitos individuais e contínuos. Estromatólitos são estruturas carbonáticas laminadas formadas pela atividade metabólica de esteiras microbianas. O estudo permitiu a identificação de 31 es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Geomorphological characteristics and seasonal variability modified the geochemistry of the lake, influencing the sedimentation and precipitation of salts and carbonates that formed biosedimentary structures of stromatolites, thrombolites, and oncoids (Silva e Silva et al, 2005, 2008.…”
Section: Sedimentary Processesmentioning
confidence: 99%
“…Geomorphological characteristics and seasonal variability modified the geochemistry of the lake, influencing the sedimentation and precipitation of salts and carbonates that formed biosedimentary structures of stromatolites, thrombolites, and oncoids (Silva e Silva et al, 2005, 2008.…”
Section: Sedimentary Processesmentioning
confidence: 99%
“…Then, Iespa et al (2012) demonstrated that it is possible to carry out a paleoenvironmental analysis on stromatolite using the petrographic technique, showing that the bioerosion and dissolution varied along the stromatolite, thus indicating changes in the lagoon, such as increased pH, reduced turbulence and water circulation and reduced biological activity, with filamentous cyanobacteria settling on the upper layer of the stromatolites. Silva et al (2013) identified 21 species of cyanobacteria in stromatolites from Lagoa Salgada, the most representative of which are Microcoleus chthonoplastes and Lyngbya aestuarii. Callefo (2014) studied biominerals as a way of understanding microbial biosignatures and Silva et al (2018) mapped microbialites types, identifying damage and threats and providing suggestions for local geoconservation.…”
Section: Study Areamentioning
confidence: 99%
“…alkaline (Dupraz et al, 2009) and precipitate carbonates (Xu et al, 2006). Silva et al (2013) identified twenty-one species of cyanobacteria in stromatolites of the Lagoa Salgada, with the most representative being Microcoleus chthonoplastes and Lyngbya aestuarii, which are diazotrophic cyanobacteria present in coastal microbial mats. In hypersaline lakes, such as Salgada, microbial mats precipitate CaCO 3 as a by-product of CO 2 capture through photosynthesis by cyanobacteria (Jonkers et al, 2003;Ludwig et al, 2005).…”
Section: 1sedimentary Processesmentioning
confidence: 99%